2016
DOI: 10.1111/1365-2435.12616
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between resprouting ability, species traits and resource allocation patterns in woody species in a temperate forest

Abstract: Summary1. Many woody plants resprout to restore above-ground biomass after disturbances or to survive in stressful environments. Resprouting requires carbohydrate storage, but the general relationship between resource allocation patterns and resprouting ability remains unclear because it can be influenced by the disturbance regime to which species have adapted. 2. We studied deciduous broadleaved trees that coexist in a Japanese cool-temperate forest to investigate the relationships among the biomass and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Shrubs, being shorter due to their multistemmed architecture, usually do not escape the flame zone. However, shrubs have higher growth rates at low size in aDGVM2, thus, they excel in postfire resprouting (Zizka et al., ), irrespective of their storage capacity (Shibata et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Shrubs, being shorter due to their multistemmed architecture, usually do not escape the flame zone. However, shrubs have higher growth rates at low size in aDGVM2, thus, they excel in postfire resprouting (Zizka et al., ), irrespective of their storage capacity (Shibata et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of these reserves is very sensitive to late-season stresses and management practices, and decreased accumulation can profoundly affect a tree's performance the following year [78]. In addition, it is reported that shade-tolerant species, such as rosewood, can regrow vigorously independent of underground reserves, with above-ground carbohydrate reserves responsible for shoot persistence in the environment after disturbance and before photosynthesis begins [43]. Applying these findings to the management of above ground biomass of rosewood, it is necessary to consider that periods of high vegetative development may represent a good time for harvesting (since there may be rapid regrowth), but during this period the plants are investing in vegetative growth and are not stocking such reserves, which is of importance to studies aiming to find the ideal period of intervention in the above ground biomass.…”
Section: Rosewood Shoots Following Above-ground Biomass Managementmentioning
confidence: 99%
“…The increase in frequency of mass loss causes changes in the content of carbohydrate stores available in reserve tissues for the production of subsequent shoots [75], while resource allocation patterns and the capacity for continuous regrowth may be influenced by the disturbance regime to which the species are adapted [43], which is unknown in the case of rosewood. Plant responses to injury are ecologically and evolutionarily important, allowing sprouting individuals to persist in the environment without changes in population size, while non-regenerating species face the challenges of seed-based regeneration, including pollination failures, the uncertainties associated with dispersion, seedling mortality, and competitive interactions while growing [33].…”
Section: Rosewood Shoots Following Above-ground Biomass Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these branches contributed little to the total basal area, they may increase photosynthesis by producing many leaves with minimal allocation of resources immediately after the fire, when the bamboo does not have any surviving aboveground parts (Kleinhenz and Midmore 2001). These characteristics seem to be adaptations that allow rapid recovery after a fire by allocating stored reserves to photosynthetic parts, as is seen during resprouting of many woody species, including shrubs (Shibata et al 2016). Since our study site has a clear dry season, fire is a frequent disturbance (typically, at least once every few years), so the production of small branches should be an effective strategy for bamboos in this area.…”
Section: Adaptation Of C Pergracile To Firesmentioning
confidence: 99%